Light-enabled reversible self-assembly and tunable optical properties of stable hairy nanoparticles - Chen, Yihuang; Wang, Zewei; He, Yanjie; Yoon, Young Jun; Jung, Jaehan; Zhang, Guangzhao; Lin, Zhiqun (Proceedings of the National Academy of Sciences - PNAS, 2018)
The ability to dynamically organize functional nanoparticles (NPs) via the use of environmental triggers (temperature, pH, light, or solvent polarity) opens up important perspectives for rapid and convenient construction of a rich variety of complex assemblies and materials with new structures and functionalities. Here, we report an unconventional strategy for crafting stable hairy NPs with light-enabled reversible and reliable self-assembly and tunable optical properties. Central to our strategy is to judiciously design amphiphilic star-like diblock copolymers comprising inner hydrophilic blocks and outer hydrophobic photoresponsive blocks as nanoreactors to direct the synthesis of monodisperse plasmonic NPs intimately and permanently capped with photoresponsive polymers. The size and shape of hairy NPs can be precisely tailored by modulating the length of inner hydrophilic block of star-like diblock copolymers. The perpetual anchoring of photoresponsive polymers on the NP surface renders the attractive feature of self-assembly and disassembly of NPs on demand using light of different wavelengths, as revealed by tunable surface plasmon resonance absorption of NPs and the reversible transformation of NPs between their dispersed and aggregated states. The dye encapsulation/release studies manifested that such photoresponsive NPs may be exploited as smart guest molecule nanocarriers. By extension, the star-like block copolymer strategy enables the crafting of a family of stable stimuli-responsive NPs (e.g., temperature- or pH-sensitive polymer-capped magnetic, ferroelectric, upconversion, or semiconducting NPs) and their assemblies for fundamental research in self-assembly and crystallization kinetics of NPs as well as potential applications in optics, optoelectronics, magnetic technologies, sensory materials and devices, catalysis, nanotechnology, and biotechnology.